Time to act on childhood obesity: the use of technology - Porri, Debora; Morabito, Letteria Anna; Cavallaro, Paola; La Rosa, Elisa; Li Pomi, Alessandra; Pepe, Giorgia; Wasniewska, Malgorzata (Frontiers in Pediatrics, 2024)
Childhood obesity is rapidly increasing worldwide and there is an urgent need to implement treatment and prevention programs. Over the last decade, in addition to increasing rates of childhood obesity, we have also observed rapid technological and digital development. The Covid-19 pandemic has largely contributed to both expansions but has also allowed an opening towards a broader vision of medicine, through new therapeutic opportunities such as mobile healthcare. The digital and technological delivery of obesity prevention and treatment programs can represent an innovative tool to support children and families to overcome some limitations and barriers such as the accessibility of programs that prevent them from adopting healthy lifestyle changes. This review aimed to summarize the impact of different digital interventions for children and adolescent affected by obesity.